Comparison of different effective mass transfer area correlation in the determination of mass transfer coefficients based on hydrodynamic analogys - Sandeep Sakhala, Shashank

Providing Decision Makers with Tailored Decision Support Systems - Kirchhoff, Jonas (The 1st Early Career Researchers Workshop Co-Located with ECSS 2021)

Textsortengeschichte - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Educational Assimilation of First-Generation and Second-Generation Immigrants in Germany - Gries, Thomas; Redlin, Margarete; Zehra, Moonum (Journal of International Migration and Integration)
Abstract Using data from the German Socio-Economic Panel for 1984–2018, we analyze the intergenerational education mobility of immigrants in Germany by identifying the determinants of differences in educational stocks for first- and second-generation immigrants in comparison to individuals without a migration background. Our results show that on average, first-generation immigrants have fewer years of schooling than native-born Germans and have a disproportionate share of lower educational qualifications. This gap is strongly driven by age at immigration, with immigration age and education revealing a nonlinear relationship. While the gap is relatively small among individuals who migrate at a young age, integrating in the school system at secondary school age leads to large disadvantages. Examining the educational mobility of immigrants in Germany, we identify an inter-generational catch-up in education. The gap in education between immigrants and natives is reduced for the second generation. Finally, we find that country of origin differences can account for much of the education gap. While immigrants with an ethnic background closer to the German language and culture show the best education outcomes, immigrants from Turkey, Italy, and other southern European countries and especially the group of war refugees from Syria, Afghanistan, Iraq and other MENA countries, have the lowest educational attainment.

Anthropogenic climate change: the impact of the global carbon budget - Redlin, Margarete; Gries, Thomas (Theoretical and Applied Climatology)
Abstract Using time series data for the period 1959–2015, our empirical analysis examines the simultaneous effects of the individual components of the global carbon budget on temperature. Specifically, we explore the possible effects of carbon emissions caused by fossil fuel combustion, cement production, land-use change emissions, and carbon sinks (here in terms of land sink and ocean sink) on climate change. The simultaneous inclusion of carbon emissions and carbon sinks allows us to look at the coexistent and opposing effects of the individual components of the carbon budget and thus provides a holistic perspective from which to explore the relationship between the global carbon budget and global warming. The results reveal a significant positive effect of carbon emissions on temperature for both fossil fuels emissions and emissions from land-use change, confirming previous results concerning carbon dioxide and temperature. Further, while ocean sink does not seem to have a significant effect, we identify a temperature-decreasing effect for land sink.

Algorithm Selection as Superset Learning: Constructing Algorithm Selectors from Imprecise Performance Data - Hanselle, Jonas Manuel; Tornede, Alexander; Wever, Marcel Dominik; Hüllermeier, Eyke

The digital home learning environment and its relation to children’s ICT self-efficacy - Bonanati, Sabrina; Buhl, Heike M. (Learning Environments Research)
With the rapid progress of technological development, self-efficacy in reference to digital devices (i.e., information and computer technology [ICT] self-efficacy) is an important driver that helps students to deal with technological problems and support their lifelong learning processes. Schools, peers, and home learning environments are important sources for the development of positive self-efficacy. Expanding on previous research, we investigated the associations between different aspects of the digital home learning environment and students’ ICT self-efficacy. The moderation effects of gender were also tested. A total of 651 children answered a questionnaire about different digital home learning environment dimensions and estimated their ICT self-efficacy using an adapted scale—Schwarzer and Jerusalem’s (1999) general self-efficacy scale. Using the structural equation modeling technique, a digital home learning environment containing six different qualities of parental support was investigated. Families’ cultural capital, parents’ attitudes toward the Internet, and shared Internet activities at home contributed positively to ICT self-efficacy. We observed small gender differences, with the moderation effect being nonsignificant. The results help researchers and practitioners to understand how different dimensions of the digital home learning environment support ICT self-efficacy. We will discuss how parents can enhance the home learning environment and how teachers can integrate this knowledge into formal education.
Keywords: Digital media use; Gender; Home learning environment; ICT self-efcacy; Motivation; Parental involvement

Latent Congruence Model to Investigate Similarity and Accuracy in Family Members' Perception: The Challenge of Cross-National and Cross-Informant Measurement (Non)Invariance - Tagliabue, Semira; Zambelli, Michela; Sorgente, Angela; Sommer, Sabrina; Hoellger, Christian; Buhl, Heike M.; Lanz, Margherita (Frontiers in Psychology)
Several methods are available to answer questions regarding similarity and accuracy, each of which has specific properties and limitations. This study focuses on the Latent Congruence Model (LCM; Cheung, 2009), because of its capacity to deal with cross-informant measurement invariance issues. Until now, no cross-national applications of LCM are present in the literature, perhaps because of the difficulty to deal with both cross-national and cross-informant measurement issues implied by those models. This study presents a step-by-step procedure to apply LCM to dyadic cross-national research designs controlling for both cross-national and cross-informant measurement invariance. An illustrative example on parent–child support exchanges in Italy and Germany is provided. Findings help to show the different possible scenarios of partial invariance, and a discussion related to how to deal with those scenarios is provided. Future perspectives in the study of parent–child similarity and accuracy in cross-national research will be discussed.
Keywords: latent congruence model; measurement invariance; similarity; accuracy; cross-national; cross-informant; parent-child relationship; support exchanges

Intergenerational Value Similarity and Subjective Well-Being - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on the association of intergenerational value similarity and adult children’s and parents’subjective well-being, on the linkage between relationship quality and subjective well-being. Mediation effects of the relationship quality on the associations between value similarity and subjective well-being were focused. The sample consisted of 600 adult German children (53.8% women) and their parents. Dyadic correlations were constructed to determine the value similarity. In this study, the general value orientation and the family values were objects of research. We measured the subjective well-being with the Satisfaction with Life Scale and we used the Network of Relationships Inventory (NRI) to measure the relationship quality. Associations between subjective well-being and value similarity, and between subjective well-being and relationship quality, as well as mediation effects, were found. All effects depend on gender and perspective.
Keywords: adult child–parent dyads; relationship quality; life satisfaction; parent–child relationship; intergenerational stake hypothesis; mediation analyses

Zusammenhang zwischen der familiären Lebenssituation und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)
Die Querschnittsuntersuchung beschäftigt sich mit der Fragestellung, ob in Zusammenhang mit der familiären Lebenssituation Erwachsener (Elternstatus und Beziehungsstatus) Unterschiede hinsichtlich der Werteähnlichkeit zwischen ihnen und ihren Eltern bestehen. Dabei wurde die Ähnlichkeit der individuellen Grundwerte nach Schwartz (1992) fokussiert. Die Werteähnlichkeit wurde mittels dyadischer Korrelationen bestimmt (Kenny & Winquist, 2001). Die Stichprobe bestand aus N= 1047 Dyaden. Dafür nahmen 600 erwachsene Kinder (53.8 % weiblich) mit ihren Eltern (542 Mütter und 505 Väter) teil. Das Alter der teilnehmenden Kinder lag zwischen 25 und 49 Jahren (M= 33.9, SD = 6.1). Die Ergebnisse dieser Studie zeigten, dass sich die Werteähnlichkeiten in Abhängigkeit von der familiären Lebenssituation unterschieden: Die Elternschaft der erwachsenen Kinder ging mit einer größeren Werteähnlichkeit in der Mutter-Kind-Dyade einher. Ebenso konnte eine größere Werteähnlichkeit zwischen verheirateten Söhnen und deren beiden Elternteilen beobachtet werden, verglichen mit den Söhnen, die Single oder in einer Partnerschaft waren. Die Werteähnlichkeit der Töchter zu ihren Eltern unterschied sich nicht in Abhängigkeit des Beziehungsstatus.

Augmented Reality als Experimentierhilfe bei Beobachtung und Deutung - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)
Keywords: digitale Medien

Suggestive Evidence for Causal Effect of Leptin Levels on Risk for Anorexia Nervosa: Results of a Mendelian Randomization Study - Peters, Triinu; Antel, Jochen; Naaresh, Roaa; Laabs, Björn-Hergen; Föcker, Manuel; Albers, Nicola; Bühlmeier, Judith; Hinney, Anke; Libuda, Lars; Hebebrand, Johannes (Frontiers in Genetics)
Genetic correlations suggest a coexisting genetic predisposition to both low leptin levels and risk for anorexia nervosa (AN). To investigate the causality and direction of these associations, we performed bidirectional two-sample Mendelian randomization (MR) analyses using data of the most recent genome-wide association study (GWAS) for AN and both a GWAS and an exome-wide-association-study (EWAS) for leptin levels. Most MR methods with genetic instruments from GWAS showed a causal effect of lower leptin levels on higher risk of AN (e.g. IVW b = −0.923, p = 1.5 × 10 −4 ). Because most patients with AN are female, we additionally performed analyses using leptin GWAS data of females only. Again, there was a significant effect of leptin levels on the risk of AN (e.g. IVW b = −0.826, p = 1.1 × 10 −04 ). MR with genetic instruments from EWAS showed no overall effect of leptin levels on the risk for AN. For the opposite direction, MR revealed no causal effect of AN on leptin levels. If our results are confirmed in extended GWAS data sets, a low endogenous leptin synthesis represents a risk factor for developing AN.
Keywords: Genetics (clinical); Genetics; Molecular Medicine

An Experimental Comparison of Explore/Exploit Strategies for the Learning Classifier System XCS - Hansmeier, Tim; Platzner, Marco (GECCO '21: Proceedings of the Genetic and Evolutionary Computation Conference Companion)

Application and modelling of ultrasonic transducers using 1-3 piezoelectric composites with structured electrodes - Dreiling, Dmitrij; Itner, Dominik; Feldmann, Nadine; Scheidemann, Claus; Gravenkamp, Hauke; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)
Waveguide-based methods can be used for the non-destructive determination of acoustic material parameters. One of these methods is based on transmission measurements of cylindrical polymeric specimens. Here, the experimental setup consists of two transducers, which excite and receive the waveguide modes at the faces of the cylinder. The measurement, as well as a forward model, are used to determine material parameters of the polymeric specimen in an inverse approach. 1-3 piezoelectric composites are used as an active element because they can be approximated by a thickness vibration only. This allows an easy identification of Mason model parameters to characterise the transducers’ vibration behaviour. However, sensitivity analysis shows a high uncertainty in the determination of the mechanical shear parameters due to the uniform excitation. To increase the sensitivity to these shear motions, arbitrary excitations were investigated by means of numerical simulation. In order to be able to realise the determined optimal excitation, new transducer prototypes were designed. By subdividing the electrodes of the active element, for example, ring-shaped excitation is feasible. Furthermore, it can be shown that modelling these transducers with a one-dimensional Mason model is sufficient.

Experimentelle Untersuchungen zum Kondensationsverhalten von Wasserdampf im Spalt zwischen Kissenplatten - Buckmann, Felix; Kenig, Eugeny

Condensation in pillow-plate heat exchangers: Experiments with pure substances - Buckmann, Felix; Kenig, Eugeny

Messverfahren für die akustische Absorption in reinen Fluiden zur Bestimmung der Volumenviskosität - Claes, Leander
Die vollständige Beschreibung fluiddynamischer und akustischer Vorgänge setzt voraus, dass die Eigenschaften des Fluids hinlänglich bekannt sind.Während Fluidkenngrößen, wie etwa die Schallgeschwindigkeit oder die Scherviskosität, für viele Flüssigkeiten über weite Bereiche des thermodynamischen Zustandsraums bekannt sind, existieren für die Volumenviskosität nur eine geringe Anzahl Messdaten.In dieser Arbeit wird daher ein Messverfahren zur selektiven Bestimmung der Volumenviskosität von Flüssigkeiten, basierend auf der Absorption von Ultraschallwellen, entwickelt und realisiert.Schwerpunkte bilden dabei der simulationsgestützte Entwurf von Algorithmen zur Auswertung der Messsignale sowie die Analyse und Weiterentwicklung einer Messanordnung, basierend auf dem Puls-Echo-Verfahren. Neben der Absorption im Fluid treten dabei weitere Effekte (zum Beispiel Beugung oder unvollständige Reflexion) auf, die das akustische Signal schwächen oder anderweitig beeinflussen. Die Entwicklung von Verfahren zur Trennung dieser Effekte von der akustischen Absorption bildet daher einen weiteren Schwerpunkt dieser Arbeit.Abschließend wird die Volumenviskosität aus der gemessenen akustischen Absorption für unterschiedliche Fluide in verschiedenen thermodynamischen Zuständen unter Zuhilfenahme anderer bekannter Fluidkenngrößen bestimmt sowie eine Unsicherheitsbetrachtung durchgeführt.

Optimal experiment design with respect to electrode configurations for a piezoelectric problem - Schulze, Veronika; Schmidt, Stephan; Jurgelucks, Benjamin; Feldmann, Nadine; Claes, Leander

Modelling damping in piezoceramics: A comparative study - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Meihost, Lars; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The progress in numerical methods and simulation tools promotes the use of inverse problems in material characterisation problems. A newly developed procedure can be used to identify the behaviour of piezoceramic discs over a wide frequency range using a single specimen via fitting simulated and measured impedances by optimising the underlying material parameters. Since there is no generally accepted damping model for piezoelectric ceramics, several mechanical damping models are examined for the material identification. Three models have been chosen and their ability to replicate the measured impedances is evaluated. On the one hand, the common Rayleigh model is considered as a reference. On the other hand, a Zener model and a model using complex constants are extended to model the transversely isotropic material. As the Rayleigh model is only valid for a limited frequency range, it fails to model the broadband behaviour of the material. The model using complex constants leads to the best fit over a wide frequency range while at the same time only adding three additional parameters for modelling damping. Thus, damping can be assumed approximately frequency-independent in piezoceramics.

Optimised Multi-Electrode Topology for Piezoelectric Material Characterisation - Claes, Leander; Feldmann, Nadine; Jurgelucks, Benjamin; Schulze, Veronika; Schmidt, Stephan; Walther, Andrea; Henning, Bernd

Piezoelectric BC Modeling for Electrode Shapes with OED - Schulze, Veronika; Schmidt, Stephan; Jurgelucks, Benjamin; Feldmann, Nadine; Claes, Leander

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse (Annales Henri Poincaré)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold M is a stochastic process that models a random perturbation of the geodesic flow. If M is an orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the L2-spectrum of the infinitesimal generator of a time-rescaled version of the process converges to the Laplace spectrum of the base manifold.

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen von Lehrkräften und ReferendarInnen am Beispiel des Schulfachs Pädagogik - Herzig, Bardo; Engemann, Mario (Fachliche Bildung und digitale Transformation - Fachdidaktische Forschung und Diskurse. Fachtagung der Gesellschaft für Fachdidaktik 2020)

Adaptive Zero-Sequence Voltage Injection for Modular Solid-State Transformer to Compensate for Asymmetrical Fault Conditions - Unruh, Roland; Lange, Jarren; Schafmeister, Frank; Böcker, Joachim (23rd European Conference on Power Electronics and Applications (EPE'21 ECCE Europe))
Modular solid-state transformers (SSTs) are a promising technology in converting power from a 10kV three-phase medium voltage to a lower DC-voltage in the range of 100…400V to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC micro grids. Modular SSTs which can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, are designed with redundant modules to increase reliability. Usually, each of the three arms operates independently, and therefore, only a fixed number of faulty modules can be compensated in each arm, even if all modules are operational in the remaining two arms. With the proposed zero-sequence voltage injection, up to 100% more faulty modules can be compensated in an arm by employing the same hardware. In addition, module power imbalances are nearly eliminated by utilizing a fundamental frequency zero-sequence voltage. A dominant 3rd harmonic zero-sequence voltage injection in combination with the 5th, 7th and several higher order harmonics with adaptive (small) amplitudes minimize the required arm voltages at steady-state. For nominal operation or symmetrical faults, the proposed technique is equivalent to the well known Min-Max voltage injection, which already reduces the peak arm voltage by 13.4% compared to a constant star point potential. A statistical analysis proves, that the expected number of tolerable faulty modules of the 1MW SST increases by 12% without the need for additional hardware.
Keywords: Solid-State Transformer; Zero sequence voltage; Fault handling strategy; Power balance control technique; Three-phase system

Das historische Schulprogramm als wissenschaftssystemische Textsorte: Reflexionen zu seiner para- und peritextuellen Ausgestaltung - Markewitz, Friedrich (Historische Text- und Diskurssemantik. Jahrbuch für Germanistische Sprachgeschichte)

Aber das Getto ist grausam, es hält seine Opfer fest in seinen faulenden Zähnen“ - Zum sprachlichen Umgang mit der drohenden Vernichtung im Diskursraum des Gettos Litzmannstadt - Markewitz, Friedrich (Sprache des Todes – Sprache des Sterbens)

Zum programmatischen Potenzial des Schulprogramms - Markewitz, Friedrich (Schulprogramme Höherer Lehranstalten. Interdisziplinäre Perspektiven auf eine wiederentdeckte bildungs- und kulturwissenschaftliche Quellengattung)

Wave Front Sets of Nilpotent Lie Group Representations - Weich, Tobias; Budde, Julia (arXiv:2103.02968v1)

Charakterisierung des Fließverhaltens von Frischbeton – Entwicklung eines adaptiven Rheometers (ACCR) und Einfluss von Maßnahmen zur Sedimentationsprävention - Pawelczyk, Sebastian; Jesinghausen, Steffen; Schmid, Hans-Joachim

Wiederholung. Zu einem temporalen und ästhetischen Muster passiv erfahrener Zeit in feuilletonistischen Städtebildern Siegfried Kracauers. - Öhlschläger, Claudia (ZfdPh, Heft 2/2021)

Digitale Zugänge zu kommunikativer Praxis schaffen: Eine explorative Interviewstudie im Projekt Sprachbegleitung Geflüchteter - Can, Magdalena; Müller, Mareike; Niederhaus, Constanze (Lockdown, Homeschooling und Social Distancing – der Zweitspracherwerb unter akut veränderten Bedingungen der COVID-19-Pandemie)
Aufgrund der Einschränkungen im Rahmen der COVID-19-Pandemie sind viele Geflüchtete von Zugängen zur Aneignung der deutschen Sprache und damit von gesellschaftlicher und bildungsbezogener Teilhabe abgeschnitten. Die vorliegende Untersuchung erkundet, inwiefern das bislang präsenzbasierte Projekt Sprachbegleitung Geflüchteter pandemiebedingt auch digital vermittelte Zugänge zu Interaktions- und Sprachlerngelegenheiten schaffen und so die Auswirkungen der gesellschaftlichen und bildungsbezogenen Isolation für Geflüchtete in Gemeinschaftsunterkünften abmildern kann. Aufbauend auf einer Fragebogenuntersuchung werden dazu die Erfahrungen und Sichtweisen drei afghanischer bzw. iranischer Geflüchteter mittels episodischer Interviews elizitiert und im Rahmen einer qualitativen Inhaltsanalyse ausgewertet. Damit wird explorativ erforscht, welche Grenzen und Chancen digitaler Zugänge zu Interaktion und kommunikativer Praxis sich skizzieren lassen und welche Konsequenzen sich für die Gestaltung von Sprachlern- und Partizipationsmöglichkeiten für Geflüchtete ableiten lassen.

Digitalisation in agriculture: Knowledge and learning requirements of German diary farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal of Research on Vocational and Educational Training)

Have Academics’ Citation Patterns Changed in Response to the Rise of World University Rankings? A Test Using First-Citation Speeds - Lee, Soo Jeung; Schneijderberg, Christian; Kim, Yangson; Steinhardt, Isabel (Sustainability)
Academics may actively respond to the expectations of the academic status market, which have largely been shaped by the World University Rankings (WURs). This study empirically examines how academics’ citation patterns have changed in response to the rise of an “evaluation environment” in academia. We regard the WURs to be a macro-level trigger for cementing a bibliometric-based evaluation environment in academia. Our analyses of citation patterns in papers published in two higher education journals explicitly considered three distinct periods: the pre-WURs (1990–2003), the period of WURs implementation (2004–2010), and the period of adaption to WURs (2011–2017). We applied the nonparametric Kaplan–Meier method to compare first-citation speeds of papers published across the three periods. We found that not only has first-citation speed become faster, but first-citation probability has also increased following the emergence of the WURs. Applying Cox proportional hazard models to first-citation probabilities, we identified journal impact factors and third-party funding as factors influencing first-citation probability, while other author- and paper-related factors showed limited effects. We also found that the general effects of different factors on first-citation speeds have changed with the emergence of the WURs. The findings expand our understanding of the citation patterns of academics in the rise of WURs and provide practical grounds for research policy as well as higher education policy.
Keywords: world university rankings; citation; first-citation speed; Minerva; Studies in Higher Education

Size Matters: The CAG Repeat Length of the Androgen Receptor Gene, Testosterone, and Male Adolescent Depression Severity - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hebebrand, Johannes; Grasemann, Corinna (Frontiers in Psychiatry)
There is a distinct increase in the prevalence of depression with the onset of puberty. The role of peripubertal testosterone levels in boys in this context is insufficiently understood and may be modulated by a functional polymorphism of the androgen receptor gene (AR), a variable number of CAG repeats. Moreover, there is preliminary evidence that the relationship between testosterone, CAG repeat length, and the severity of depressive symptoms may differ between subclinical and overt depression, but this has neither been studied in a clinical sample of adolescents with depression nor compared between subclinical and overt depression in an adequately powered study. To investigate the relationship between free testosterone, CAG repeat length of the AR, depression status (subclinical vs. overt), and the severity of depressive symptoms, 118 boys treated as in- or daycare patients at a single psychiatric hospital were studied. Of these, 73 boys had at least mild depressive symptoms according to the Beck Depression Inventory-II (BDI-II > 13). Higher-order moderation analysis in the multiple regression framework revealed a constant relationship between free testosterone and depression severity irrespective of the number of CAG repeats in adolescents with a BDI-II score ≤ 13. In adolescents with a BDI-II score > 13, however, there was a significant negative relationship between free testosterone and BDI-II score in patients with <19 CAG repeats and a significant positive relationship regarding free testosterone and BDI-II score in those with more than 28 CAG repeats, even when considering important covariates. These results suggest that the effects of testosterone on mood in male adolescents with depression depend on the genetic make-up of the AR as well as on depression status. This complex relationship should be considered by future studies addressing mental health issues against an endocrine background and may, moreover, contribute to tailored treatment concepts in psychiatric medicine, especially in adults.

Vitamin D Level Trajectories of Adolescent Patients with Anorexia Nervosa at Inpatient Admission, during Treatment, and at One Year Follow Up: Association with Depressive Symptoms - Föcker, Manuel; Timmesfeld, Nina; Bühlmeier, Judith; Zwanziger, Denise; Führer, Dagmar; Grasemann, Corinna; Ehrlich, Stefan; Egberts, Karin; Fleischhaker, Christian; Wewetzer, Christoph; Wessing, Ida; Seitz, Jochen; et al. (Nutrients)
(1) Background: Evidence has accumulated that patients with anorexia nervosa (AN) are at higher risk for vitamin D deficiency than healthy controls. In epidemiologic studies, low 25(OH) vitamin D (25(OH)D) levels were associated with depression. This study analyzed the relationship between 25(OH)D serum levels in adolescent patients and AN and depressive symptoms over the course of treatment. (2) Methods: 25(OH)D levels and depressive symptoms were analyzed in 93 adolescent (in-)patients with AN from the Anorexia Nervosa Day patient versus Inpatient (ANDI) multicenter trial at clinic admission, discharge, and 1 year follow up. Mixed regression models were used to analyze the relationship between 25(OH)D levels and depressive symptoms assessed by the Beck Depression Inventory (BDI-II). (3) Results: Although mean 25(OH)D levels constantly remained in recommended ranges (≥50 nmol/L) during AN treatment, levels decreased from (in)patient admission to 1 year follow up. Levels of 25(OH)D were neither cross-sectionally, prospectively, nor longitudinally associated with the BDI-II score. (4) Conclusions: This study did not confirm that 25(OH)D levels are associated with depressive symptoms in patients with AN. However, increasing risks of vitamin D deficiency over the course of AN treatment indicate that clinicians should monitor 25(OH)D levels.

Alterations in B cell subsets correlate with body composition parameters in female adolescents with anorexia nervosa - Freff, Jana; Schwarte, Kathrin; Bröker, Lisa; Bühlmeier, Judith; Kraft, Isabelle; Öztürk, Dana; Hinney, Anke; Arolt, Volker; Dannlowski, Udo; Romer, Georg; Baune, Bernhard T.; Hebebrand, Johannes; et al. (Scientific Reports)
Abstract Anorexia nervosa (AN) is a severe eating disorder and often associated with altered humoral immune responses. However, distinct B cell maturation stages in peripheral blood in adolescents with AN have not been characterized. Treatment effects and the relationship between clinical and B cell parameters are also not fully understood. Here we investigated the phenotype of circulating B cell subsets and the relationship with body composition in adolescents with AN before (T0, n = 24) and after 6 weeks (T1, n = 20) of treatment. Using multi-parameter flow cytometry, we found increased percentages of antigen-experienced B cells and plasmablasts in patients with AN compared to healthy controls (n = 20). In contrast, percentages of CD1d + CD5 + B cells and transitional B cells with immunoregulatory roles were reduced at T0 and T1. These B cell frequencies correlated positively with fat mass, fat mass index (FMI), free fat mass index, and body mass index standard deviation score. In addition, scavenger-like receptor CD5 expression levels were downregulated on transitional B cells and correlated with fat mass and FMI in AN. Our findings that regulatory B cell subgroups were reduced in AN and their strong relationship with body composition parameters point toward an impact of immunoregulatory B cells in the pathogenesis of AN.

Kurzzeitige Behandlung von Patient_innen mit Anorexia nervosa mit rekombinant hergestelltem Human-Leptin (Metreleptin): Rasch einsetzende positive Effekte auf Stimmung, Kognition und Verhalten - Hebebrand, Johannes; Antel, Jochen; Tan, Susanne; Wabitsch, Martin; Wiesing, Urban; Barth, Nikolaus; Ludwig, Christine; Bühlmeier, Judith; Libuda, Lars; Milos, Gabriella; Hinney, Anke (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie)

Vom ‚Komaglotzen‘ zum literar- und medienästhetischen Lernen. Konzeptualisierung eines fernsehseriellen Lehr-Lern-Settings am Beispiel des Teen Dramas ANNE WITH AN E. - Kißling, Magdalena (Der Deutschunterrich (2))

Intermedialer Literaturunterricht. Ein medienintegratives Differenzierungskonzept zur Förderung literarästhetischen Lernens am Beispiel ausgewählter Kinderromane für die Sekundarstufe I - Kißling, Magdalena (Medienwissenschaften und Mediendidaktik im Dialog – Zum Status Quo von Medienbildung im Deutschunterricht)

Einleitung - Kißling, Magdalena (Kinder- und Jugendliteratur intermedial. Unterrichtsanregungen und -materialien zum literarischen Lernen im Medienverbund anhand von Emil und die Detektive (Gym/Ge) und Jakob der Lügner (BK). Erstellt von Masterstudierenden der Universität Paderborn)

Passivität als Widerstand gegen die Macht der Verhältnisse? "Bartleby, the scrivener" aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft)

Inklusives Klassenklima. Zur Bedeutung der sozialen Dimension des Klassenklimas unter Berücksichtigung von Heterogenität - Knickenberg, Margarita; Stöcker, A; Zurbriggen, Carmen (Inklusive Schule und Schulentwicklung Theoretische Grundlagen, empirische Befunde und Praxisbeispiele aus Deutschland, Österreich und der Schweiz.)

Die Bedeutsamkeit von Peers für Jugendliche in der Sekundarstufe und in der Freizeit - Knickenberg, Margarita; Zurbriggen, Carmen (G. Hagenauer & D. Raufelder (Hrsg.), Soziale Eingebundenheit. Sozialbeziehungen im Fokus von Schule und Lehrer*innenbildung)

Pädagogikunterricht und Digitalisierung: fachliches Lernen digital und digitales Lernen fachlich denken - Martin, A.; Herzig, Bardo (Pädagogik Unterricht: Die Fachzeitschrift für die pädagogische Fächergruppe)

Medienbildung in Schule und Unterricht - Tulodziecki, G.; Herzig, Bardo; Grafe, S.

Wie wirksam ist das Lernen mit digitalen Medien? Einblicke in den Stand der Forschung - Herzig, Bardo (SchulVerwaltung spezial)

Examination of hazardous situations in industrial closed-loop processes using dynamic simulations - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Dynamic simulation of hazardous situations in industrial closed loop processes considering chemical absorption - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Die Bedeutung von Intertextualität für die Beschreibung der historischen Textsorte Schulprogramm. Zu Text-Text- sowie Text-Textwelt-Beziehungen - Markewitz, Friedrich (Intertextualität. Vom Zitat zur Anspielung in Texten der deutschen Sprache vom 8. bis zum 19. Jahrhundert)

Umsetzbarkeit des Wortschatzsammler-Therapiekonzepts bei Kindern mit Trisomie 21. Eine qualitative Einzelfallstudie - Glowania, M; Lassmann, I; Ulrich, Tanja (Praxis Sprache)

Kasusfähigkeiten mehrsprachiger Achtjähriger. Eine explorative Pilotstudie in Regelgrundschulen - Ulrich, Tanja; Thater, S; Mennicken, S (Logos)

A lower bound on the displacement of particles in 2D Gibbsian particle systems - Richthammer, Thomas; Fiedler, Michael (Stochastic Processes and their Applications)
While 2D Gibbsian particle systems might exhibit orientational order resulting in a lattice-like structure, these particle systems do not exhibit positional order if the interaction between particles satisfies some weak assumptions. Here we investigate to which extent particles within a box of size may fluctuate from their ideal lattice position. We show that particles near the center of the box typically show a displacement at least of order . Thus we extend recent results on the hard disk model to particle systems with fairly arbitrary particle spins and interaction. Our result applies to models such as rather general continuum Potts type models, e.g. with Widom–Rowlinson or Lenard-Jones-type interaction.

Full Version -- Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (arXiv:2108.02109)
Consider a set of jobs connected to a directed acyclic task graph with a fixed source and sink. The edges of this graph model precedence constraints and the jobs have to be scheduled with respect to those. We introduce the Server Cloud Scheduling problem, in which the jobs have to be processed either on a single local machine or on one of many cloud machines. Both the source and the sink have to be scheduled on the local machine. For each job, processing times both on the server and in the cloud are given. Furthermore, for each edge in the task graph, a communication delay is included in the input and has to be taken into account if one of the two jobs is scheduled on the server, the other in the cloud. The server can process jobs sequentially, whereas the cloud can serve as many as needed in parallel, but induces costs. We consider both makespan and cost minimization. The main results are an FPTAS with respect for the makespan objective for a fairly general case and strong hardness for the case with unit processing times and delays.

Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas

Gattung und Geschlecht. Weibliche Tragödienheldinnen in Lessings Emilia Galotti? - Süwolto, Leonie (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas)

Moderne Heldin im antiken Gewand? Anne Webers „Annette, ein Heldinnenepos“ - Süwolto, Leonie (blog interdisziplinäre geschlechterforschung)

Topographien der Vergänglichkeit. Vanitas, Alter und Gesellschaft bei Monika Maron und Martin Walser - Süwolto, Leonie (Vanitas und Gesellschaft)

Einleitung - Schlieper, Hendrik (Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft)

Genealogische Spuren in Racines Phèdre - Schlieper, Hendrik (Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft)

Helden-Geschlechter: Die Bérénice-Tragödien Corneilles und Racines - Schlieper, Hendrik (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas. (culturae, 21))

Tendres conquêtes: l’Amérique galante selon Rameau et Fuzelier (Les Indes galantes, 1735) - Schlieper, Hendrik (Amérique(s) poétique(s) entre Ancien et Nouveau Monde. L’espace américain comme nouveau territoire de la fiction de Fontenelle à Chateaubriand. Révolutions et Romantismes, 27))

Gattung und Geschlecht: Überlegungen zu einem kulturstiftenden Paradigma - Schlieper, Hendrik (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas)

Sophonisbe: alea et agôn, genre tragique et gender. Les en-jeux diversifiés de la politique et de l’amour - Schlieper, Hendrik (Corneille présent, 1)

Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft

James Bond - mit Vergil gesehen: "Dr. No" (1962) - Steigerwald, Jörn (Komparatistik heute. Aktuelle Positionen der vergleichenden Literatur- und Kulturwissenschaft)

La tragedia amorosa dell'"Adone" ossia il nuovo ordinamento dell’amore - Steigerwald, Jörn (L’“Adone“ di Giovan Battista Marino. Mito - Movimento - Maraviglia. Atti del convegno internazionale (Humboldt-Universität zu Berlin, 1-2 luglio 2019))

Corneille maître du jeu ou la dramatologie novatrice de „Rodogune" - Steigerwald, Jörn (Corneille présent n° 1, 2021, Corneille: un théâtre où la vie est un jeu)

Von der Liebestragödie zur Tragödie der Liebe: Jean Racines „Phèdre" - Steigerwald, Jörn (Literaturwissenschaftliches Jahrbuch 62)

Erklärtexte lesen und schreiben. Praxis Deutsch 285

Textprozeduren und der Erwerb literaler Kompetenz - Rezat, Sara; Feilke, Helmuth (Sprach(en)erwerb. Der Deutschunterricht. Koch, Nikolas/Kozikowski, Barbara (Hrsg.))

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas D (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Zur makrostrukturellen Prägung argumentierender Textprozeduren - Rezat, Sara (ar|gu|men|tie|ren. Eine zentrale Sprachhandlung im Fach- und Sprachunterricht)

Digitale Desinformation und Fake News. Schülerinnen und Schüler erklären, warum Fake News sich so gut verbreiten - Rezat, Sara; Arnold, Cynthia (Praxis Deutsch 285)

Erklärtexte lesen und schreiben. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch 285)

When water becomes an integral part of carbon – combining theory and experiment to understand the zeolite-like water adsorption properties of porous C2N materials - Heske, Julian Joachim; Walczak, Ralf; Epping, Jan D.; Youk, Sol; Sahoo, Sudhir K.; Antonietti, Markus; Kühne, Thomas; Oschatz, Martin (Journal of Materials Chemistry A)
The origin of strong interactions between water molecules and porous C 2 N surfaces is investigated by using a combination of model materials, volumetric physisorption measurements, solid-state NMR spectroscopy, and DFT calculations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Hydrogen bond dynamics of interfacial water molecules revealed from two-dimensional vibrational sum-frequency generation spectroscopy - Ojha, Deepak; Kühne, Thomas (Scientific Reports)
Abstract Vibrational sum-frequency generation (vSFG) spectroscopy allows the study of the structure and dynamics of interfacial systems. In the present work, we provide a simple recipe, based on a narrowband IR pump and broadband vSFG probe technique, to computationally obtain the two-dimensional vSFG spectrum of water molecules at the air–water interface. Using this technique, to study the time-dependent spectral evolution of hydrogen-bonded and free water molecules, we demonstrate that at the interface, the vibrational spectral dynamics of the free OH bond is faster than that of the bonded OH mode.
Keywords: Multidisciplinary

Organic Mixed-Valence Compounds and the Overhauser Effect in Insulating Solids - Pylaeva, Svetlana; Marx, Patrick; Singh, Gurjot; Kühne, Thomas; Roemelt, Michael; Elgabarty, Hossam (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Artificial Neural Networks as Trial Wave Functions for Quantum Monte Carlo - Kessler, Jan; Calcavecchia, Francesco; Kühne, Thomas (Advanced Theory and Simulations)
Keywords: Multidisciplinary; Modeling and Simulation; Numerical Analysis; Statistics and Probability

Artificial neural networks for the kinetic energy functional of non-interacting fermions - Ghasemi, Alireza; Kühne, Thomas (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

A combinatorial study of electrochemical anion intercalation into graphite - Chugh, Manjusha; Jain, Mitisha; Wang, Gang; Nia, Ali Shaygan; Mirhosseini, Hossein; Kühne, Thomas (Materials Research Express)
Abstract Dual-ion batteries are considered to be an emerging viable energy storage technology owing to their safety, high power capability, low cost, and scalability. Intercalation of anions into a graphite positive electrode provides high operating voltage and improved energy density to such dual-ion batteries. In this work, we have performed a combinatorial study of graphite intercalation compounds considering four anions, namely hexafluorophosphate (PF <?CDATA ${}_{6}^{-}$?> 6 − ), perchlorate (ClO <?CDATA ${}_{4}^{-}$?> 4 − ), bis(fluorosulfonyl)imide (FSI − ), and bis(trifluoromethanesulfonyl)imide (TFSI − ), via first-principles calculations. The structural properties and energetics of the intercalation compounds are compared based on different sizes, geometries, and the physical and chemical properties of the intercalated anions. The staging mechanism of anion intercalation into graphite and the specific capacities, and voltage profiles of the intercalated compounds are investigated. A comparison regarding battery electrochemistry is also done with available experimental observations. Our calculated intercalation energies and voltage profiles show that the initial anion intercalation into graphite is less favorable than subsequent ones for all the anions considered in this study. Although the effect of the size of anions in a graphite cathode on various properties of the intercalated compounds is not as significant as the size of cations in a graphite anode, some distinction between the studied anions can still be made. Among the studied anions, the intercalation compounds based on PF <?CDATA ${}_{6}^{-}$?> 6 − are the most stable ones. These PF <?CDATA ${}_{6}^{-}$?> 6 − anions cause relatively small structural deformations of the graphite and have the highest oxidative ability, highest onset voltage, and highest diffusion barrier along the graphene sheets. The overall small diffusion barriers of the anions within graphite explain the high rate capability of dual-ion batteries.
Keywords: Metals and Alloys; Polymers and Plastics; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Full Assignment of Ab-Initio Raman Spectra at Finite Temperatures Using Wannier Polarizabilities: Application to Cyclohexane Molecule in Gas Phase - Partovi-Azar, Pouya; Kühne, Thomas (Micromachines)
We demonstrate how to fully ascribe Raman peaks simulated using ab initio molecular dynamics to specific vibrations in the structure at finite temperatures by means of Wannier functions. Here, we adopt our newly introduced method for the simulation of the Raman spectra in which the total polarizability of the system is expressed as a sum over Wannier polarizabilities. The assignment is then based on the calculation of partial Raman activities arising from self- and/or cross-correlations between different types of Wannier functions in the system. Different types of Wannier functions can be distinguished based on their spatial spread. To demonstrate the predictive power of this approach, we applied it to the case of a cyclohexane molecule in the gas phase and were able to fully assign the simulated Raman peaks.
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Control and Systems Engineering

Photocatalytic Water Splitting Reaction Catalyzed by Ion-Exchanged Salts of Potassium Poly(heptazine imide) 2D Materials - Sahoo, Sudhir K.; Teixeira, Ivo F.; Naik, Aakash; Heske, Julian Joachim; Cruz, Daniel; Antonietti, Markus; Savateev, Aleksandr; Kühne, Thomas (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

Ultrafast solvent-to-solvent and solvent-to-solute energy transfer driven by single-cycle THz electric fields - Balos, Vasileios; Elgabarty, Hossam; Wolf, Martin; Kühne, Thomas; Netz, Roland; Bonthuis, Douwe Jan; Kaliannan, Naveen; Loche, Philip; Kampfrath, Tobias; Sajadi, Mohsen (Terahertz Emitters, Receivers, and Applications XII)

A theoretical investigation of topological phase modulation in carbide MXenes: Role of image potential states - Wang, Mengying; Ranjbar, Ahmad; Kühne, Thomas; Belosludov, Rodion V.; Kawazoe, Yoshiyuki; Liang, Yunye (Carbon)
Keywords: General Chemistry; General Materials Science

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Testing as an approach to control the Corona epidemic dynamics and avoid lockdowns - Gries, Thomas; Welfens, Paul J. J. (International Economics and Economic Policy)
Abstract Vaccinations, lockdowns and testing strategies are three potential elements of an effective anti-coronavirus, and in particular Covid-19, health policy. The following analysis considers - within a simple model - the potentially crucial role of a Corona testing approach in combination with a quarantine approach which is shown herein to be a substitute for broad lockdown measures. The cost of lockdowns/shutdowns are rather high so that – beyond progress in terms of a broad vaccination program – a rational testing strategy should also be carefully considered. Testing has to be organized on the basis of an adequate testing infrastructure which could largely be implemented in firms, schools, universities and public administration settings. As regards the cost of a systematic broad Covid-19 testing strategy, these could come close to 0.5% of national income if there are no vaccinations. The Testing & Quarantine approach suggested here – with tests for symptomatic as well as asymptomatic people - is based on a random sampling and would require rather broad and frequent testing; possibly one test per person every 7–10 days. At the same time, one should consider that the cost of further lockdowns/shutdowns of a duration of 1 month could be very high, such that a standard cost benefit analysis supports the testing approach suggested herein. Also, an optimal policy mix could be designed where both vaccinations and testing play a crucial role. As of late January 2021, no further lockdowns in Germany and other OECD countries would be necessary if a broad testing infrastructure can be established rather quickly. This in turn will reinforce economic optimism and help to jumpstart economic growth in Europe, the US and Asia in a solid way. The basic logic of the testing approach pointed out here for industrialized countries could also be applied in developing countries. The approach presented is complementary to the IMF analysis of Cherif/Hasanov.
Keywords: Economics and Econometrics

Extreme Events, Entrepreneurial Start-Ups, and Innovation: Theoretical Conjectures - Gries, Thomas; Naudé, Wim (Economics of Disasters and Climate Change)
Abstract In light of the COVID-19 pandemic, we scrutinize what has been established in the literature on whether entrepreneurship can cause and resolve extreme events, the immediate and long-run impacts of extreme events on entrepreneurship, and whether extreme events can positively impact (some) entrepreneurship and innovation. Based on this, we utilize a partial equilibrium model to provide several conjectures on the impact of COVID-19 on entrepreneurship, and to derive policy recommendations for recovery. We illustrate that while entrepreneurship recovery will benefit from measures such as direct subsidies for start-ups, firms’ revenue losses, and loan liabilities, it will also benefit from aggregate demand-side support and income redistribution measures, as well as from measures that facilitate the innovation-response to the Keynesian supply-shock caused by the pandemic, such as access to online retail and well-functioning global transportation and logistics.
Keywords: General Medicine

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; López-Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Influence of different ester side groups in polymers on the vapor phase infiltration with trimethyl aluminum - Mai, Lukas; Maniar, Dina; Zysk, Frederik; Schöbel, Judith; Kühne, Thomas; Loos, Katja; Devi, Anjana (Dalton Transactions)
The influence of different polymer side chains on the vapor phase infiltration with TMA is investigated and supported by DFT-calculations.
Keywords: Inorganic Chemistry

Integrated and Iterative Requirements Analysis and Test Specification: A Case Study at Kostal - Wiecher, Carsten; Fischbach, Jannik; Greenyer, Joel; Vogelsang, Andreas; Wolff, Carsten; Dumitrescu, Roman (arXiv preprint)

Drift Detection in Text Data with Document Embeddings - Feldhans, Robert; Wilke, Adrian; Heindorf, Stefan; Shaker, Mohammad Hossein; Hammer, Barbara; Ngonga Ngomo, Axel-Cyrille; Hüllermeier, Eyke (Intelligent Data Engineering and Automated Learning – IDEAL 2021)

Convolutional Hypercomplex Embeddings for Link Prediction - Demir, Caglar; Moussallem, Diego; Heindorf, Stefan; Ngonga Ngomo, Axel-Cyrille (The 13th Asian Conference on Machine Learning, ACML 2021)
Knowledge graph embedding research has mainly focused on the two smallest normed division algebras, $\mathbb{R}$ and $\mathbb{C}$. Recent results suggest that trilinear products of quaternion-valued embeddings can be a more effective means to tackle link prediction. In addition, models based on convolutions on real-valued embeddings often yield state-of-the-art results for link prediction. In this paper, we investigate a composition of convolution operations with hypercomplex multiplications. We propose the four approaches QMult, OMult, ConvQ and ConvO to tackle the link prediction problem. QMult and OMult can be considered as quaternion and octonion extensions of previous state-of-the-art approaches, including DistMult and ComplEx. ConvQ and ConvO build upon QMult and OMult by including convolution operations in a way inspired by the residual learning framework. We evaluated our approaches on seven link prediction datasets including WN18RR, FB15K-237 and YAGO3-10. Experimental results suggest that the benefits of learning hypercomplex-valued vector representations become more apparent as the size and complexity of the knowledge graph grows. ConvO outperforms state-of-the-art approaches on FB15K-237 in MRR, Hit@1 and Hit@3, while QMult, OMult, ConvQ and ConvO outperform state-of-the-approaches on YAGO3-10 in all metrics. Results also suggest that link prediction performances can be further improved via prediction averaging. To foster reproducible research, we provide an open-source implementation of approaches, including training and evaluation scripts as well as pretrained models.

Generating Physically Sound Training Data for Image Recognition of Additively Manufactured Parts - Nickchen, Tobias; Heindorf, Stefan; Engels, Gregor (2021 IEEE Winter Conference on Applications of Computer Vision (WACV))

Automatically generating instructions from tutorials for search and user navigation - Heindorf, Stefan

SecuCheck: Engineering configurable taint analysis for software developers - Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

IDE Support for Cloud-Based Static Analyses - Luo, Linghui; Schäf, Martin; Sanchez, Daniel; Bodden, Eric (Proceedings of the 29th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Software Engineering)

SootFX: A Static Code Feature Extraction Tool for Java and Android - Karakaya, Kadiray; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

Integrated superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Verma, Varun B; Protte, Maximilian; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Ebers, Lena; Hammer, Manfred; Förstner, Jens; Silberhorn, Christine; Mirin, Richard P; Woo Nam, Sae; et al. (Journal of Physics: Photonics)
We demonstrate the integration of amorphous tungsten silicide superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides. We show proof-of-principle detection of evanescently coupled photons of 1550 nm wavelength using bidirectional waveguide coupling for two orthogonal polarization directions. We investigate the internal detection efficiency as well as detector absorption using coupling-independent characterization measurements. Furthermore, we describe strategies to improve the yield and efficiency of these devices.

Gesellschaftliche Transformationen durch die Steigerung (popmusik)kultureller Teil-habe mittels innovativer Preiskonzepte – ein interdisziplinärer Literaturüberblick - Müller, Stefanie Jutta Marianne; Kundisch, Dennis